Radiocarbon Dates from the Highland Jar and Coffin Burial Site of Phnom Khnang Peung, Cardamom Mountains, Cambodia. Issue 1 (2015) - Beavan, Nancy; Hamilton, Derek; Sokha, Tep; Sayle, Kerry
Abstract : The Cardamom Mountain Jar and Coffin burial site of Phnom Khnang Peung is the most extensive example of the distinctive burial ritual first reported by Beavan et al. (2012a). The 40 intact Mae Nam Noi and late Angkorian-era ceramic jars used as burial vessels held a total of up to 152 individuals, representing the largest corpus of skeletal remains of any of the 10 known Jar and Coffin burial sites that have been discovered in the eastern ranges of the Cardamom Mountains of Cambodia. We report here on the radiocarbon dating of this site and notable burial phenomena, using a Bayesian approach to model the start and end date of activity as well as its overall span. The results of the dating and Bayesian analyses indicate that the Phnom Khnang Peung site's earliest burials began cal AD 1420–1440 ( 95% probability ). Interestingly, the concentration of burial activity spans only 15–45 years ( 95% probability ), despite the large number of inhumations at the site. The 14 C chronology presented for the site places the Highland burial ritual coincident with a period of economic, political, and societal transformations in the lowland Angkorian polity, but the unique burial practice and trade relationships evidenced by the burial goods and maritime trade ware ceramics employed in the burial ritual suggest these Highland people were a culture apart from Angkorian cultural influences.